2011
DOI: 10.1159/000330404
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Mitral Stenosis and Left Ventricular Mechanics: A Speckle Tracking Study

Abstract: Background: It has been shown that mitral stenosis (MS) impairs left ventricular (LV) systolic function; however, this issue has not been studied comprehensively. We aimed to evaluate the role of 2D strain in the assessment of subclinical LV systolic dysfunction in patients with MS. Methods: Seventy-two patients with isolated MS (mild, moderate and severe) and 31 healthy control subjects constituted the study population. 2D echocardiography images were obtained from LV apical 4-chamber (4C), long axis (LAX), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 51 publications
4
32
0
Order By: Relevance
“…In addition, the fact that the systolic parameters such as IVA and Sm velocities are not correlated with MVA and the mean gradient, though weakly associated with IVV, indicates that the LV systolic dysfunction might be caused by an acute rheumatic fever leading to myocardial damage. The results of some studies [12,30] were consistent with these findings in that the major determinant of the LV systolic dysfunction in isolated MS is impaired contractility and not the hemodynamic factors. Lee and Lee [12] evaluated the LV myocardium of 15 isolated MS patients using electron microscopy and demonstrated structural changes in LV independent from the EF and the degree of MS, determined by ECHO parameters.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, the fact that the systolic parameters such as IVA and Sm velocities are not correlated with MVA and the mean gradient, though weakly associated with IVV, indicates that the LV systolic dysfunction might be caused by an acute rheumatic fever leading to myocardial damage. The results of some studies [12,30] were consistent with these findings in that the major determinant of the LV systolic dysfunction in isolated MS is impaired contractility and not the hemodynamic factors. Lee and Lee [12] evaluated the LV myocardium of 15 isolated MS patients using electron microscopy and demonstrated structural changes in LV independent from the EF and the degree of MS, determined by ECHO parameters.…”
Section: Discussionsupporting
confidence: 63%
“…However, these patients with abnormal LV function always exhibit more extensive loss of myofibrils which results from either disproportion of the mitochondria-to-myofibril ratio or myofibrillar degeneration. In the study of Bilen et al [30], which investigated the LV systolic function of mild, moderate and severe MS patients with preserved EF, using 2D speckle-tracking ECHO-derived strain; it was demonstrated that LV longitudinal function was decreased in patients with MS compared to the controls, however, this decrease was independent from the degree of MS. In our study, LV systolic function was evaluated globally with TDI-derived IVA and similar results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…10 There was significantly reduced LV GLS in patients with MS compared with healthy controls (-13.10±3.67% versus -22.17±2.30, P=0.0001). This is in agreement with the studies of Bilenet al and Sengupta et al 6,11 In order to test an underlying myocardial factor responsible for this decrease, in the present study we compared regional LV longitudinal strain in the study group versus healthy control group. The presence of significant decrease in LV basal and mid-segmental strain values compared with healthy control group and less or non-significant decrease in apical segments point out to possible underlying myocardial factor where rheumatic endocarditis and scarring extend from the mitral annulus to the surrounding LV segments.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the other commonly encountered valve lesions (mitral regurgitation, aortic stenosis, and aortic regurgitation), MS does not produce any significant hemodynamic load on the left ventricle, and therefore, left ventricle (LV) systolic dysfunction is pretty uncommon in the setting of MS. However, a few studies have reported that LV systolic dysfunction may not be so uncommon in patients with rheumatic MS. 5,6 Right ventricular (RV) function plays an important role in development of clinical symptoms and prognosis in patients with MS. This is primarily because of hemodynamic effect on RV due to pulmonary hypertension.…”
mentioning
confidence: 99%
“…The emergence of 2-dimensional speckletracking echocardiography has further circumvented some of the limitations of Doppler in registering 1-dimensional angle-dependent data [12] . A study by Bilen et al [13] in the latest issue of Cardiology employed 2-dimenisonal speckle-tracking echocardiography for assessing of LV deformation in a large cohort of patients with varying degrees of MS. Authors reported abnormalities in LV deformation, and suggested that the contractile abnormalities were independent of hemodynamic severity of MS. Like previous investigations, the pathophysiological explanation for the occurrence of myocardial contrac-…”
mentioning
confidence: 99%